STUDI TINGKAT EROSI DAERAH ALIRAN SUNGAI LUMPO KECAMATAN IV JURAI KABUPATEN PESISIR SELATAN - Marnil, Sepka; Edial, Helfia; Juita, Erna (Pendidikan Geografi, 2013)
This research study aims to determine the Watershed Erosion Rate LumpoKecamatan IV Jurai South Coastal District. The method used in this research is descriptive method is to give an idea of the character of the object studied and compared between each other in order to obtain the desired conclusion, sampling method in this study is the method of sample areas (sampling area), where the unit of measurement is each lithological units derived from the geological map with consideration of land use (vegetation cover), slope and soil type. The results showed that: (1) The level of erosion in the study area is divided into 2 parts low Qal.1.Sw.Lat lithological units and lithological units Qal.1.Sm.Lat, while the rate of erosion was the lithological units Tomp.III . Sw.Lat, Tomp.III.Kc.Lat and Tomp.V.Ht.Lat, (2) There were no differences in erosion rate based on land use (agriculture and plantation) in each different lithological units in the watershed Lumpo and (3) there were no differences in erosion rate by land use (agriculture and plantation) in each unit of the same lithology in watershed Lumpo.